1573. Discrepancies Between Premortem and Postmortem Diagnoses of Infectious Diseases Found on Autopsy in Hematopoietic Cell Transplantation Recipients at a High-Volume Academic Transplant Center. (26th November 2018) - Multani, Ashrit; Allard, Libby; Wangjam, Tamna; Sica, R Alejandro; Epstein, David J; Rezvani, Andrew; Ho, Dora
Abstract: Background: Hematopoietic cell transplantation (HCT) is a potentially curative treatment option for patients with hematologic malignancies and other diseases but carries a significant risk of infection-related morbidity and mortality. Many of these infections are difficult to diagnose and treat. It is not infrequent that HCT recipients die from infection despite extensive investigations and broad-spectrum antimicrobial therapy. Autopsy is the gold standard for establishing the cause of death but rates of performing autopsies are decreasing despite their immense value. We present the most recent case series of infectious diseases found on autopsy in HCT recipients at our high-volume academic transplant center. Methods: We retrospectively reviewed the medical charts and autopsy records of 131 HCT recipients who underwent autopsy between January 1, 2000 and December 31, 2016. The premortem clinical diagnoses as documented by the clinical teams were compared with autopsy findings. Discrepancies were identified and classified according to the Goldman Criteria (NEJM 1983; 308:1000–5). Results: A total of 4, 072 patients received 4, 395 transplants between January 1, 2000 and December 31, 2016. Of the 1, 937 patients who died, 131 (7%) had an autopsy performed. Of these 131 patients, 24 (18%) patients had a total of 29 infections that were identified only postmortem; 4 (3%) patients had >1 such infection. Of these 29 infections, 15 (52%) were viral, 9 (31%) were fungal, 3 (10%) were bacterial, and 2 (7%) were parasitic; no mycobacterial infections were found. According to the Goldman Criteria, 22 (76%) had class I discrepancies ("major diagnoses for which detection before death would in all probability have led to a change in management that might have resulted in cure or prolonged survival"). Illustrative cases of each infection type will be presented to highlight the challenges of infection management in HCT. Conclusion: Autopsies of HCT recipients frequently identify clinically significant infections which were not suspected pre-mortem. Our study reinforces the educational value of the autopsy, which is underutilized but can be employed to help prevent future similar infectious complications and improve patient outcomes. Disclosures: All authors: No reported disclosures.